International Public Lecture talked about Business Engineering - UMP, PNC
Universiti Malaysia Pahang (UMP), being a technology-based university, organised an international public lecture titled, ‘The Convergence: Business Engineering’ delivered by Reutlingen University (RU) President, Professor Dr. Hendrik Brumme.